The bird sisters eaudiobook - Rasmussen, Rebecca (Tantor Media, 2012)
When a bird flies into a window in Spring Green, Wisconsin, sisters Milly and Twiss get a visit. Twiss listens to the birds' heartbeats, assessing what she can fix and what she can't, while Milly listens to the heartaches of the people who've brought them. These spinster sisters have spent their lives nursing people and birds back to health. But back in the summer of 1947, Milly and Twiss knew nothing about trying to mend what had been accidentally broken. Milly was known as a great beauty with emerald eyes and Twiss was a brazen wild child who never wore a dress or did what she was told. That was the summer their golf pro father got into an accident that cost him both his swing and his charm, and their mother, the daughter of a wealthy jeweler, finally admitted their hardscrabble lives wouldn't change. It was the summer their priest, Father Rice, announced that God didn't exist and ran off to Mexico, and a boy named Asa finally caught Milly's eye. And, most unforgettably, it was the summer their cousin Bett came down from a town called Deadwater and changed the course of their lives forever. Rebecca Rasmussen's masterfully written debut novel is full of hope and beauty, heartbreak and sacrifice, love and the power of sisterhood, and offers wonderful surprises at every turn.